THE RELATIONSHIP OF EDUCATION AND LEADER BEHAVIOR WITH PERFORMANCE OF EMPLOYEES AT THE SECRETARIAT OFFICE OF THE LEBONG REGENCY - Yeti Inarti; Suwarni; Rinto Noviantoro (Penerbit Jurnal Indonesia, 2020)
Target of this research is to know relation Education and leadership with the performance of goverment employees at the Secretariat Office of hall of people Representative of Lebong Recency. Method Analysis the used is correlation of rank hypothesis test and spearman with comparison of value of rho test. relationwhich is signifikan between education and training with officer performance at Secretariat Office of hall of people Representative of Lebong Recency.